Optimalisasi Manajemen Kinerja Guru dalam Meningkatkan Mutu Pendidikan Islam: Optimizing Teacher Performance Management in Improving the Quality of Islamic Education - Sutrisna, Vivi Afianti; Rohmadi, Syamsul Huda (STAI Publisistik Thawalib Jakarta, 2024)
Good teacher performance has a positive impact on the quality of learning, as reflected in students' academic achievements. This study aims to analyze the school's efforts to improve teacher performance, identify the challenges faced, and evaluate professional development programs. Using a qualitative method with a phenomenological approach, the research was conducted through observations, interviews, and document studies at Sompokan Seyegan State Elementary School, Yogyakarta. The data processing involved condensation, presentation, and conclusion drawing, while ensuring data validity through triangulation and confirmability. The findings indicate that optimizing teacher performance requires skill adjustment and training to align with the